Provincial heterogeneity in the management of care cascade for hypertension, diabetes, and dyslipidaemia in China: Analysis of nationally representative population-based survey - Zhao, Yang; Anindya, Kanya; Atun, Rifat; Marthias, Tiara; Han, Chunlei; McPake, Barbara; Duolikun, Nadila; Hulse, Emily; Fang, Xinyue; Ding, Yimin; Oldenburg, Brian; Lee, John Tayu (Frontiers in Cardiovascular Medicine, 2022)
Background This study aims to examine 1) province-level variations in the levels of cardiovascular disease (CVD) risk and behavioural risk for CVDs, 2) province-level variations in the management of cascade of care for hypertension, diabetes, and dyslipidaemia, and 3) the association of province-level economic development and individual factors with the quality of care for hypertension, diabetes, and dyslipidaemia. Methods We used nationally representative data from the China Health and Retirement Longitudinal Study in 2015, which included 12,597 participants aged 45 years. Using a care cascade framework, we examined the quality of care provided to patients with three prevalent NCDs: hypertension, diabetes, and dyslipidaemia. The proportion of WHO CVD risk based on the World Health Organisation CVD risk prediction charts, Cardiovascular Risk Score (CRS) and Behaviour Risk Score (BRS) were calculated. We performed multivariable logistic regression models to determine the individual-level drivers of NCD risk variables and outcomes. To examine socio-demographic relationships with CVD risk, linear regression models were applied. Results In total, the average CRS was 4.98 (95 percent CI: 4.92, 5.05), while the average BRS was 3.10. (95 percent confidence interval: 3.04, 3.15). The weighted mean CRS (BRS) in Fujian province ranged from 4.36 to 5.72 (P<0.05). Most of the provinces had a greater rate of hypertension than diabetes and dyslipidaemia awareness and treatment. Northern provinces had a higher rate of awareness and treatment of all three diseases. Similar patterns of regional disparity were seen in diabetes and dyslipidaemia care cascades. There was no evidence of a better care cascade for CVDs in patients who reside in more economically advanced provinces. Conclusion Our research found significant provincial heterogeneity in the CVD risk scores and the management of the cascade of care for hypertension, diabetes, and dyslipidaemia for persons aged 45 years or more. To improve the management of cascade of care and to eliminate regional and disparities in CVD care and risk factors in China, local and population-based focused interventions are necessary.